1992
DOI: 10.1152/ajpendo.1992.262.1.e110
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids in the CNS regulate BAT metabolism and plasma insulin in ob/ob mice

Abstract: Adrenalectomy stimulates depressed brown adipose tissue (BAT) metabolism and decreases hyperinsulinemia in ob/ob mice, with minimal effects in lean mice. A single intracerebroventricular injection of dexamethasone (250 ng) into adrenalectomized ob/ob mice completely reversed the effects of adrenalectomy on BAT thermogenesis as assessed by mitochondrial GDP binding, approximately doubled plasma insulin, lowered whole body metabolic rates by 17%, and increased food intake by 19%. These responses were rapid in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…Of note is the observation that Y2 receptor deficiency also reduced the responsiveness of mice to exogenous corticosterone administration. In wild-type mice, corticosterone administration resulted in an obesity syndrome, which has been observed by other investigations of rats (6) and mice (38). This finding may be related to the fact that glucocorticoids are known to increase NPY mRNA and͞or peptide levels and Y receptor expression in the hypothalamus in vivo (6,39) and in vitro (39).…”
Section: Discussionsupporting
confidence: 68%
“…Of note is the observation that Y2 receptor deficiency also reduced the responsiveness of mice to exogenous corticosterone administration. In wild-type mice, corticosterone administration resulted in an obesity syndrome, which has been observed by other investigations of rats (6) and mice (38). This finding may be related to the fact that glucocorticoids are known to increase NPY mRNA and͞or peptide levels and Y receptor expression in the hypothalamus in vivo (6,39) and in vitro (39).…”
Section: Discussionsupporting
confidence: 68%
“…48 Thus, the failure of RU-486 to fully correct hyperinsulinemia in ob/ob mice may have prevented complete restoration of b 3 -AR expression. Given that adrenalectomy or RU-486 treatment at younger ages is more effective in correcting hyperinsulinemia in obese rodents, 10,11,14,31 it will be interesting to see if a similar experimental approach will fully restore b 3 -AR expression. Recent work has shown that b 3 -AR expression is also modulated by thyroid status.…”
Section: Ru-486 Ameliorates Diabetesmentioning
confidence: 99%
“…6 In MSG-treated rats high levels of corticosterone have also been described 7,8 and this is probably related to the central (via sympathetic nervous system) or directly suppresive effect of glucocorticoids on brown adipose tissue (BAT) activity. 9,10 In most types of obese animals, BAT is in a thermogenically quiescent and relatively atrophied state. Recently, reduced GLUT4 in BAT was found in both 30 and 90 day old MSG-treated rats.…”
Section: Introductionmentioning
confidence: 99%